2013
DOI: 10.1097/pcc.0b013e318297622f
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Newborn Infants With Severe Respiratory Failure Before and After Establishing an Extracorporeal Membrane Oxygenation Program*

Abstract: The establishment of an extracorporeal membrane oxygenation program was associated with a significant increase in the survival of newborns more than or equal to 35 weeks old with severe hypoxic respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 24 publications
0
13
0
3
Order By: Relevance
“…24 Recent studies have reported that infants with AKI had a longer length of stay and mechanical ventilation in the NICU, 1,4 but we found the reverse regarding both NICU length of stay and respiratory support required. These differences could be explained by noting that in our study, non-surviving infants had a median hospital duration significantly shorter than those who survived (3 days [IQR: 3-10] versus 21 days [IQR: [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], respectively, p < 0.01).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…24 Recent studies have reported that infants with AKI had a longer length of stay and mechanical ventilation in the NICU, 1,4 but we found the reverse regarding both NICU length of stay and respiratory support required. These differences could be explained by noting that in our study, non-surviving infants had a median hospital duration significantly shorter than those who survived (3 days [IQR: 3-10] versus 21 days [IQR: [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], respectively, p < 0.01).…”
Section: Discussionmentioning
confidence: 72%
“…17,18 Unfortunately, ECMO is not available in our hospital due to its very high cost, although studies from developed countries have found that this treatment can significantly increase the survival rate of PPHN. 19,20 Also, again due to financial restrictions, our hospital has and had at the time of the study only a limited number of neonatal nurses, with three to four critically ill infants usually being cared for by only one nurse. One of the notable causes of high mortality in our PPHN infants was CDH/pulmonary hypoplasia (seven of nine infants, 77.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, particles of aspirated meconium cause airway obstruction contributing to a deterioration of respiratory function. Therefore, patients with MAS have significant hypoxemia, hypercarbia, and respiratory acidosis, which further aggravates damage of lung parenchyma, leading to pulmonary vasoconstriction, and an increase in right-to-left pulmonary shunts (Kattan et al 2013). In experimental animals with meconium instillation, a similar battery of symptoms leading to a significant deterioration in lung function can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Al comparar el período antes y después del establecimiento de este programa ECMO en Chile, se encontró que la sobrevida del grupo total de RN con insuficiencia respiratoria grave (IO > 25) aumentó significativamente desde un 75% (75/100) en el período pre-ECMO a un 91% (67/74) en el período ECMO, especialmente en el grupo de RN con hernia diafragmática congénita 27 (HDC). Durante el período ECMO, un 70% de estos pacientes con insuficiencia respiratoria grave fueron rescatados con iNO y/o VAFO, mientras que un 30% no mejoraron, ingresando a ECMO un 76% de estos últimos 27 .…”
Section: Pronóstico Y Programas Ecmo En Latinoaméricaunclassified
“…Durante el período ECMO, un 70% de estos pacientes con insuficiencia respiratoria grave fueron rescatados con iNO y/o VAFO, mientras que un 30% no mejoraron, ingresando a ECMO un 76% de estos últimos 27 .…”
Section: Pronóstico Y Programas Ecmo En Latinoaméricaunclassified